A South Indian Cadaveric Study on the Prevalence of Gallstones - Nayak, S. B.; Soumya, K. V. (Kathmandu University Medical Journal, 2020)
Background Gallstone disease (GSD) is one among the most prevalent diseases that affects approximately 10-15% of the population. It is associated with many other diseases like gallbladder cancer, renal stones, atherosclerosis, coronary heart disease and stroke. Objective Objective of this study is to document the prevalence of gallstones among south Indian cadavers. Method One hundred and twenty three South Indian cadaveric livers/gallbladders were observed for the presence of gallstones. The age range was 40 to 70 years. The gallbladders were palpated to know the presence of stones. They were then dissected and the stones were classified based on appearance. Gall bladder walls were also observed to know the associated fibrosis. Result Among the cadavers studied, 0.81% possessed cholesterol stones and 4.06% had pigment stones. Among the stones, 83.33% were pigment stones and 16.66% were cholesterol stones. Conclusion Compared to the western countries and north Indian studies, the prevalence of gallstone disease is low in the south Indian population (4.87%). The low prevalence was probably due to the low socioeconomic status and the diet and lifestyle.